Consumer satisfaction about hospital services: A study from the outpatient department of a private medical college hospital at Mangalore - Prasanna K; Bashith M; Sucharitha S (Wolters Kluwer Medknow Publications, 2009)
Background: Consumer satisfaction is an important parameter for assessing the quality of patient care services. There is a need to assess the health care systems regarding the consumer satisfaction as often as possible. Objectives: To assess the consumer satisfaction regarding the services provided in our outpatient department in terms of clinical care, availability of services, waiting time, and cost. Materials and Methods: A 27-item pre-tested questionnaire was given to 100 patients (caretakers in pediatric patients) at the end of their O.P.D visit from 3 to 4 pm for 5 days from November 7, 2005 to November 11, 2005. The items in the questionnaire referred to particulars of the patients such as age, sex, occupation, department requested, lab, and medical stores. While analyzing, they were grouped into categories like availability, clinical care, waiting time, and cost. The responses were expressed in proportions. Results: The availability of services and clinical care was found to be satisfactory. 81% of the respondents found the communication by the doctor good, 97% of the respondents were satisfied about the explanation of the disease by the doctor The average time required for consulting the doctor was 46.5 ± 20.9 min. But when time spent in pharmacy was considered, it was not significantly satisfactory. The cost of investigation was significantly moderate or high in 97% of the respondents. Conclusions: Recommendations are required for reduction of time spent in the pharmacy and the cost of investigations to improve consumer satisfaction.